2022
DOI: 10.3389/fnins.2022.926629
|View full text |Cite
|
Sign up to set email alerts
|

New Retinal Pigment Epithelial Cell Model to Unravel Neuroprotection Sensors of Neurodegeneration in Retinal Disease

Abstract: Retinal pigment epithelial (RPE) cells sustain photoreceptor integrity, and when this function is disrupted, retinal degenerations ensue. Herein, we characterize a new cell line from human RPE that we termed ABC. These cells remarkably recapitulate human eye native cells. Distinctive from other epithelia, RPE cells originate from the neural crest and follow a neural development but are terminally differentiated into “epithelial” type, thus sharing characteristics with their neuronal lineages counterparts. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Cellular regulation of RPE phagocytosis can be studied in cell cultures by challenging RPE cells (primary culture as well as ARPE-19 cells) with isolated POS [ 9 , 29 , 30 , 31 ]. In addition, it has been reported that RPE cells can mediate non-specific phagocytosis by engulfing latex beads, for example [ 9 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cellular regulation of RPE phagocytosis can be studied in cell cultures by challenging RPE cells (primary culture as well as ARPE-19 cells) with isolated POS [ 9 , 29 , 30 , 31 ]. In addition, it has been reported that RPE cells can mediate non-specific phagocytosis by engulfing latex beads, for example [ 9 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cellular regulation of RPE phagocytosis can be studied in cell cultures by challenging RPE cells (primary culture as well as ARPE-19 cells) with isolated POS [ 9 , 29 , 30 , 31 ]. In addition, it has been reported that RPE cells can mediate non-specific phagocytosis by engulfing latex beads, for example [ 9 , 29 , 32 ]. To study the effect of HG on ARPE-19 cells phagocytic function, they were seeded in 96-well plates and exposed to HG (33 mM) for 24, 48, or 72 h. Then, non-specific phagocytosis was measured using pHrodo™ green E. coli BioParticles ® , as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations